Anti-inflammatory effects of methanol extracts from the Antarctic lichen, Amandinea sp. in LPS-stimulated raw 264.7 macrophages and zebrafish. Issue 107 (December 2020) - Kim, Jung Eun; Min, Seul Ki; Hong, Ju-Mi; Kim, Kyung Hee; Han, Se Jong; Yim, Joung Han; Park, Hyun; Kim, Il-Chan
Abstract: The aim of the present study was to determine the anti-inflammatory effect of an extracts isolated from the lichen. Amandinea sp. was collected from the Antarctic and extracted with methanol. The basic screening of the anti-inflammatory property of the extracts was done using the NO assay. The extracts showed very little cytotoxicity, and reduced NO production in LPS-stimulated RAW 264.7 cells in a dose-dependent manner. Furthermore, the extracts inhibited LPS-induced release of pro-inflammatory cytokines such as interleukin-6 (IL-6), and tumor necrosis factor-α(TNF-α), and inflammatory mediators inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2). The extracts also reduced the cytosolic p -IκB-α level and the level of the nuclear factor p65. We examined the anti-inflammatory effects of the extracts using zebrafish in vivo . The extracts reduced the amount of reactive oxygen species (ROS) in LPS-induced zebrafish larvae and inhibited the mRNA expression of inflammatory cytokines and mediators in a tail-cutting induced model. These results are similar to those obtained in vitro with RAW 264.7 cells. Collectively, the data suggest that the extracts may contain one of more compounds with anti-inflammatory effects. Further studies are required to identify the candidate compound/s and to understand the mechanism of action of the extract. Highlights: We analyzed the anti-inflammatory effect of an extract isolated from the Antarctic lichen Amandinea sp. In-vitro LPS-stimulated RAW 264.7 macrophages and an in vivo zebrafish model were used. The extract decreases the concentration of inflammatory cytokine and mediators.